Developing the Console Dash: a 2D Adventure Game using Godot Game Engine - Retno, Sujacka; Fortilla, Zeny Arsya; Sinambela, Ilmi Suciani (Gameology and Multimedia Expert, 2024)
A 2D platformer game, console dash is a game that tells the story of Dax, a curious game character, jumping out of his console to go on an adventure. He goes through difficult levels, collects objects and meets new friends. They form a team and fight a villain named Glitch. The aim of this research is to design a 2D Console Dash platformer game with an adventure genre that is interesting and also quite difficult to complete. This application was created using the Godot game engine with the GDScript programming language. The method used in this final assignment uses the MDLC model software development method, and uses the SWOT method for system weakness analysis. The final result of this project is a 2D platformer game that plays smoothly and provides an enjoyable gaming experience. Console Dash offers attractive graphics, music and sound effects that liven up the atmosphere of the game, as well as challenging levels to explore. Moreover, this game has an intuitive interface and responsive controls.